Antibacterial Activity of a Novel Peptide-Modified Lysin Against Acinetobacter baumannii and Pseudomonas aeruginosa - Yang, Hang; Wang, Mengyue; Yu, Junping; Wei, Hongping (Frontiers in Microbiology, 2015)
The global emergence of multidrug-resistant (MDR) bacteria is a growing threat to public health worldwide. Natural bacteriophage lysins are promising alternatives in the treatment of infections caused by Gram-positive pathogens, but not Gram-negative ones, like Acinetobacter baumannii and Pseudomonas aeruginosa, due to the barriers posed by their outer membranes. Recently, modifying a natural lysin with an antimicrobial peptide was found able to break the barriers, and to kill Gram-negative pathogens. Herein, a new peptide-modified lysin (PlyA) was constructed by fusing the cecropin A peptide residues 1–8 (KWKLFKKI) with the OBPgp279 lysin and its antibacterial activity was studied. PlyA showed good and broad antibacterial activities against logarithmic phase A. baumannii and P. aeruginosa, but much reduced activities against the cells in stationary phase. Addition of outer membrane permeabilizers (EDTA and citric acid) could enhance the antibacterial activity of PlyA against stationary phase cells. Finally, no antibacterial activity of PlyA could be observed in some bio-matrices, such as culture media, milk, and sera. In conclusion, we reported here a novel peptide-modified lysin with significant antibacterial activity against both logarithmic (without OMPs) and stationary phase (with OMPs) A. baumannii and P. aeruginosa cells in buffer, but further optimization is needed to achieve broad activity in diverse bio-matrices.